Cochrane’s contribution to global health: three decades of progress in sickle cell disease research - Martí-Carvajal, Arturo (Frontiers in Hematology, 2025)
BackgroundSickle cell disease (SCD) is a significant global health challenge, disproportionately affecting populations in low-resource regions, particularly sub-Saharan Africa, India, the Mediterranean, and the Caribbean. The Cochrane Collaboration has significantly contributed to evidence synthesis in SCD management, yet its impact has not been comprehensively assessed.Research questionHow has Cochrane’s evidence synthesis shaped research outputs and identified gaps in clinical evidence for SCD?ObjectiveTo systematically evaluate the scope, methodological rigour, and evidence gaps within Cochrane reviews on SCD interventions (1996–2024) and identify areas requiring further research.MethodsWe analysed 49 Cochrane systematic reviews using a mixed-methods approach, assessing both abstracted data and full-text methodology where available. Our quantitative analyses examined randomised clinical trials (RCTs), participant numbers, and meta-analytical techniques. We conducted qualitative analyses encompassing thematic categorisation and geographic distribution evaluation.ResultsOur analysis revealed significant methodological gaps: 34.7% (17/49) of reviews contained no RCTs (‘empty’ reviews), and notably, none of the 32 reviews incorporating RCTs conducted meta-analyses. Among the 32 reviews with RCTs, the median number of included trials was 3 (IQR: 1.75–5), with a median of 260 participants (IQR: 112–555). The research concentrated in three primary domains: Pain Management and Complications (22 reviews), Infection Prevention and Transfusion (15 reviews), and Genetic Therapies and Nutritional Support (12 reviews). The UK and Venezuela have produced the largest number of Cochrane reviews on SCD, positioning them as the primary contributors to evidence synthesis in this field. Additionally, 67.4% (33/49) of reviews involved international collaboration, reflecting a substantial degree of cross-border research engagement.ConclusionsCochrane reviews on SCD exhibit critical methodological limitations, particularly the absence of meta-analyses and the high prevalence of empty reviews. These gaps underscore the urgent need for enhanced primary research, especially RCTs, in underexplored therapeutic areas. Geographical analysis suggests opportunities for expanding international collaboration, particularly with researchers from high-burden, low-resource settings. To strengthen evidence-based SCD management, future research must prioritise: (1) standardising outcome measures, (2) applying innovative systematic review methodologies, and (3) closing identified evidence gaps. Addressing these issues will enhance the quality, reliability, and clinical applicability of systematic reviews in SCD research.